Multiple mountain‐hopping colonization of sky‐islands on the two sides of Tropical Africa during the Pleistocene: The afroalpine Festuca grasses. (15th April 2021) - Mairal, Mario; Namaganda, Mary; Gizaw, Abel; Chala, Desalegn; Brochmann, Christian; Catalán, Pilar
Abstract: Aim: The afroalpine sky‐islands present one of the most interesting models to study discrete biogeographic patterns in a terrestrial island system. Here, we performed range‐wide sampling of the afroalpine clade of fine‐leaved Festuca grasses and address a set of hypotheses on its origin and dispersal. We focus on the widespread species F . abyssinica and explore the role of the eastern and western African sky‐islands. Location: Tropical Africa. Taxon: Afroalpine Festuca . Methods: We combine data from field surveys, phylogeography, coalescence‐based dispersal modelling, and environmental niche and dispersal costs analyses to infer patterns of genetic diversity, genealogical relationships, colonization routes and range shifts under two Quaternary climates (current – to represent warm periods; and Last Glacial Maximum (LGM) – to represent cold periods). Results: The westernmost populations in East Africa show higher genetic diversity and higher similarities with the West African populations and the Ethiopian Simen Mountains than with the more closely situated East African populations. Dispersal models and ecological niche predictions of F. abyssinica supported multiple long‐distance dispersals (LDD) among the eastern African sky‐islands, and at least two dispersal events between the two sides of Africa (0.86 Ma and 0.52 Ma), probably facilitated by bridging suitable habitats during the coldest periods of the Pleistocene. Main conclusions: We reconstruct an afroalpine mountain‐hopping dispersal model, with migrations occurring between adjacent sky‐islands in eastern Africa, and through a Central Africa–Sudan pathway connecting afroalpine patches on the two sides of the continent.